2018
DOI: 10.1108/jhlscm-07-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the design of refugee camps

Abstract: Purpose -An unprecedented scale of human migration has lead humanitarians to view camps as long-term settlements rather than temporary holding facilities. The purpose of this paper is to increase the understanding of and identify challenges with this proposed new approach to camp design. Design/methodology/approach -Based on the camp design literature, the authors developed an interview guide and checklist for data collection. A multi-site case study and within-and cross-case analysis was then conducted. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…The refugee in-flows have initiated not only innovated curricula but also innovation services, technologies and methodologies that, with appropriate planning, could bring a multiplier effect in the university, the refugees, their home countries, and in Greek society. The modernization of camps is a necessary step closer to socio-economic integration, environmental sustainability, and consistency with local development plans (Jahre et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The refugee in-flows have initiated not only innovated curricula but also innovation services, technologies and methodologies that, with appropriate planning, could bring a multiplier effect in the university, the refugees, their home countries, and in Greek society. The modernization of camps is a necessary step closer to socio-economic integration, environmental sustainability, and consistency with local development plans (Jahre et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The camp design and development followed a traditional approach of centralized decision-making (Jahre et al 2018), with some traces of new approaches such as the trials of environmental impact assessment (waste control via recycling, gardening, etc.). The chronicity of crisis is visible in the various projects in the camps (related to education, social integration, entertainment, culture) as its structures become more permanent rather than temporary and where relationships and future plans start to follow long-term concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Study [21] has shown that refined design principles for refugee camps must support spatial planning and natural resource sustainability while minimizing tension and accounting for the needs, perspectives, and integration of refugees and host communities [1]. Figure 1 below identifies the proposed approach for a refugee camp design managing time, space and resources.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…Motivated by the sudden need for refugee management, different countries utilized different approaches. Jahre et al (2018) analyze four different refugee camps, each having their own dynamics, in Ethiopia, Kenya, Greece and Turkey. The first two are actually not related with the Syrian crisis, pointing out the fact that refugee camps are actually not new to the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have been conducted on the scope of refugee management in the operations research (OR) literature so far. There are many reports forming an established gray literature ( Jahre et al, 2018). How to link this literature to OR remains an open venue for further research.…”
Section: Introductionmentioning
confidence: 99%